Effects of Long-Term Use of Depomedroxy Progesterone Acetate on Serum Lipids - Ferdous, Shahrin; Amir, Mumtahena; Chowdhury, Saleha Begum; Nasrin, Begum; Hamid, Farzana; Banu, Shabnam (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Introduction: Long Acting Reversible Contraceptive (LARC) is one of the most popular method of family planning. The Aim of the study was to explore the effects of long-term use of Depomedroxyprogesterone acetate (DMPA) which is the most commonly used LARC, on serum lipid profile. Methods: This cross-sectional analytical study was carried out in the Department of Obstetrics and Gynaecology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, during the period December 2015 to September 2016. A total 70 married women at the age range of 20-35 years attending, the family planning clinic of BSMMU were included in this study. Out of them 35 subjects who had been using DMPA for ³ two years uninterruptedly were considered as cases and another 35 subjects who did not use any hormonal contraceptives were labeled as control. In both the groups, age and BMI were matched. All the study subjects in both groups were apparently healthy. Fasting blood samples were collected from each subject for the estimation of Total Cholesterol (TC), Triglyceride (TG), High-density Lipoprotein Cholesterol (HDLC) and Low-density Lipoprotein Cholesterol (LDLC). The data were collected in a pre-designed data sheet and analyzed with student T-test for the statistical significance. Results: Serum TC and LDLC level in group-I (cases) were significantly higher compared to group-II (control) and the difference was statistically significant (p<0.05). Serum High-density Lipoprotein Cholesterol (HDLC) level in group-I was lower than group-II which was also statistically significant (p=0.001). Serum Triglyceride level in group-I was higher than group- II, however the difference was not statistically significant (p=0.177). Conclusion: DMPA use for ³ two years increases serum TC and LDLC and decrease serum HDLC, which may increase the risk of atherosclerosis. Bangladesh J Obstet Gynaecol, 2019; Vol. 34(2): 106-111